O princípio constitucional do desenvolvimento sustentável: análise da sua concretização no Estado do Rio Grande do Norte - Silva Júnior, Ivanaldo Soares da (2009)
The Article 225 of Constitution of the Federative Republic of Brazil in its main body, stipulates that everyone is entitled to ecologically balanced environment and the use of common people and essential to the healthy quality of life, should be imposed on public authorities and the community the duty to defend it and preserve it for present and future generations. Following a universal trend, the letter raised the Brazilian environment the category of one of those values ideals of social order, dedicating it, along with a constitution of rules sparse, a chapter, itself, which definitely, institutionalized the right to healthy environment as a fundamental right of the individual. The national public policies and state should be in line with modern theories of Sustainable Development, outlined within the international society, and certainly instruments that should be made effective through the mobilization of civil society as a whole. The implementation of Human Rights, in fact, depends on a strong political action and not just a legal problem. Thus, this work of theoretical-descriptive nature we will address various dimensions of sustainable development, such as environmental education, water, sanitation, health and sustainable development plans, evaluating its current stage in our state